TEACHER COGNITION AND EARLY MULTILITERACIES PEDAGOGY IMPLEMENTATION IN EFL CONTEXT - R. Rizkiki Azkia Hidayat; Wawan Gunawan; Budi Hermawan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigates the initial implementation of multiliteracies pedagogy (MLP) in an English as a Foreign Language (EFL) classroom in Indonesia. Although the increasing complexity of language learning requires innovative pedagogical approaches, many EFL classrooms continue to rely on conventional teaching practices. In addition, limited studies have explored how teachers initially understand and apply MLP proposed by the New London Group in EFL contexts. Using a single-case qualitative design, this study involved one English teacher at an Indonesian senior high school. Data were collected through pre- and post-implementation interviews, classroom observations, and lesson plan documentation. The data were analyzed thematically to examine changes in teacher cognition and instructional practices during the implementation process. The findings indicate that the teacher’s understanding of pedagogy developed from a procedural focus on activities and media toward a more conceptual and pedagogically informed perspective. This shift was reflected in lesson design, questioning strategies, classroom interaction, and the teacher’s role in facilitating students’ meaning-making. Furthermore, the implementation process became a significant site for professional learning, fostering reflective and student-centered teaching practices. The study contributes to the growing discussion of MLP in EFL education by emphasizing the importance of supporting teachers in translating pedagogical frameworks into effective classroom practice and professional development.